Understanding the international trade of Colombians: empirical evidence from the theory of comparative advantages (2000-2022) - Peláez Soto, José Tomás (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
The article contributes to the correct understanding of the international exchange of Colombians from the main teaching of the theory of comparative advantages, namely: exports to import. In addition to a solid theoretical framework, this teaching seeks to illustrate through an econometric regression by ordinary least squares. Empirical evidence showed that, indeed, imports depend on exports. It was found that a 1.0% increase in exports led to a 0.57% increase in imports between 2000-2022. It was also found that incoming remittances had a positive influence on imports: a 1.0% increase in remittances boosted imports by 0.25%. On the other hand, direct foreign investment did not influence imports. In general terms, the article provides evidence that allows, among other things, to refute the mercantilist conception of international exchange.